Intelligence and obesity during the obesity epidemic - Rebecca B. Clarke; Gunhild T. Okholm; Erik L. Mortensen; Merete Osler; Cathrine L. Wimmelmann; Thorkild I. A. Sørensen (Scientific Reports)
Abstract Several studies conducted during the last 50 years have shown that lower intelligence is associated with a higher body mass index (BMI). During this period, the prevalence of obesity and overweight has increased considerably. We investigated whether this increase has altered the relation between intelligence and BMI by studying two cohorts of 419,319 conscripts, born 1939–1959 and 1983–2001, examined in the same geographical districts in Denmark. While the prevalence of obesity increased from 0.8% in the early to 6.7% in the late cohort, the two cohorts showed essentially the same pattern of relations between intelligence test scores (ITS), prevalence of obesity and overweight (including obesity), and BMI. The prevalence of obesity and overweight and BMI was higher at any ITS value in the late than in the early cohort, but inversely associated with ITS in both cohorts. The ITS displayed inverse J-shaped associations with BMI, with ITS peaking around a BMI of 20 kg/m2 and declining with higher BMI, although with a somewhat steeper decline in the early than in the late cohort. Thus, irrespective of the increase in prevalence of obesity and overweight and in BMI, the pattern of inverse relations between intelligence and higher BMI levels was maintained.